Budaya sebagai Mekanisme Pembentukan Identitas dan Interaksi Sosial: A Systematic Literature Review dalam Konteks Multikultural - Rosada Rosada; Angga Setiawan; Riang Darmawan CM; Oom Rohmah Syamsudin (Journal of Leadership, Organization, Vision, and Administration, 2026)
Globalization has intensified intercultural interactions; however, previous studies have predominantly treated culture as a determinant of behavior without comprehensively examining the underlying conceptual mechanisms. This study aims to analyze and synthesize the role of culture in shaping identity, behavior, and social interactions within multicultural societies. A Systematic Literature Review (SLR) was conducted using the PRISMA framework, with literature retrieved from Google Scholar and ScienceDirect covering the period from 2021 to 2026. Of the 259 articles initially identified, 10 met the inclusion criteria and were selected for analysis. The findings reveal that culture operates through three primary mechanisms: value internalization, identity construction, and the regulation of social interactions, all of which are further influenced by structural factors. This study proposes a multidimensional conceptual framework that elucidates the role of culture in shaping identity and social interaction. These findings advance the understanding of culture as an active system that continuously influences social dynamics within multicultural societies.